Pengembangan Media Pembelajaran Interaktif Berbasis Genially pada Subtema Pemanfaatan Kekayaan Alam di Indonesia - Siska Rahmawati; Ratih Purnamasari; Roy Efendi (STKIP Andi Matappa Pangkep, 2023)
This research aims to develop genially-based learning media in the sub-theme of utilizing natural wealth in Indonesia to determine the feasibility of these products. This research uses the R&D (Research and Development) research method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results showed that the interactive learning media developed was very suitable for use as a learning media in class IV-B of SDN Mekarjaya 10 Depok city in learning based on the average validation score of media experts 85.33%, the average validation score of linguists was 81.33%, and the average validation score of material with criteria of 85.33%, the validation results were included in the category of “very feasible” to use. Based on the student response questionnaire of 85.45%, it is included in the “very good” category.